Attitudes Toward Inclusive Education: An Exploration of the Interaction Between Teachers’ Status and Students’ Type of Disability Within the French Context - Jury, Mickaël; Perrin, Anne-Laure; Rohmer, Odile; Desombre, Caroline (Frontiers in Education, 2021)
Teachers’ positive attitudes towards inclusive education appears to be necessary to successfully implement this policy. The present research, conducted within the French context, seeks to replicate previous findings regarding students’ type of disability or teachers’ status and extend them by specifically examining the interaction between these two variables. We notably hypothesized (1) that teachers’ attitudes will be the least positive for students with autism spectrum disorder, in comparison with students with cognitive disorder and students with motor impairment; (2) that special education teachers will have more positive attitudes than general teachers; and more importantly, (3) that special education teachers, in comparison with general teachers, would be less likely to express distinct attitudes depending on students’ type of disability. An online questionnaire was completed by 311 teachers. Results replicated previous findings by showing that teachers’ attitudes were more favorable towards students with motor impairment than students with cognitive disorder or than students with autism spectrum disorder. In addition, taking into account the teacher’s status, results showed that if special education teachers had more positive attitudes than general teachers, they however expressed less favorable attitudes towards the inclusion of students with autism spectrum disorder in comparison with those with other type of disability. These results are notably discussed regarding the lay beliefs associated with students with autism spectrum disorder and the influence of training.